1994
DOI: 10.1042/bj2970585
|View full text |Cite
|
Sign up to set email alerts
|

NADPH-cytochrome c reductase from human neutrophil membranes: purification, characterization and localization

Abstract: Neutrophil-membrane-associated NADPH-cytochrome c reductase and cytochrome b558 were separately eluted and highly purified by a combination of ion-exchange Sepharose, N-amino-octylagarose, 2',5'-ADP-Sepharose and heparin-Sepharose column chromatographies. The purified cytochrome c reductase with an apparent molecular mass of 68 kDa contained FMN and FAD (FMN/FAD approx. 1). Cytochrome b558 prepared in the presence of phospholipids and FAD showed marked O2-.-producing activity (Vmax., 8.53 mumol of O2-./min per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 44 publications
1
16
0
Order By: Relevance
“…We examined this by adding reagent FAD or a FAD-rich NBT-reductase fraction, previously demonstrated to be obligatory to reconstitute the NADPH oxidase activity of purified cytochrome b 558 without added reagent FAD (41). In this rationale, the NBT-reductase fraction providing flavoproteins with NADPH-(30) and flavin-binding sites would work like cytochrome P-450 reductase, bypassing electrons to heme(s) in cytochrome b 558 , rebuilding electron transfer machinery (41,(43)(44)(45). This approach would indicate whether or not at least interaction with an exogenous dehydrogenase could be achieved and give indications on the patient's heme functional status.…”
mentioning
confidence: 99%
“…We examined this by adding reagent FAD or a FAD-rich NBT-reductase fraction, previously demonstrated to be obligatory to reconstitute the NADPH oxidase activity of purified cytochrome b 558 without added reagent FAD (41). In this rationale, the NBT-reductase fraction providing flavoproteins with NADPH-(30) and flavin-binding sites would work like cytochrome P-450 reductase, bypassing electrons to heme(s) in cytochrome b 558 , rebuilding electron transfer machinery (41,(43)(44)(45). This approach would indicate whether or not at least interaction with an exogenous dehydrogenase could be achieved and give indications on the patient's heme functional status.…”
mentioning
confidence: 99%
“…CO inhibits the major components of endogenous oxidantgenerating machinery, NADPH oxidase, and the cytochrome-c oxidase of the mitochondrial respiratory chain, and thereby blocks formation of ROS (25,27). In our present study, a slight decrease of TASK-1 current on the application of CO or ascorbic acid might reflect a positive modulation of TASK-1 by the basal production of ROS.…”
Section: Interpretation Of the Effects Of Co On Hypoxia-⌬i Task-1mentioning
confidence: 53%
“…It was initially supposed that the replacement of heme-bound O 2 with CO might exert a hypoxia-like effect by deterring the ROS generation from NOX4 (25,27). When cells were pretreated with CO (1%, see MATERIALS AND METHODS), however, the CO treatment only weakly decreased I TASK-1 (8 Ϯ 3.5%, n ϭ 5).…”
Section: Effects Of Co and Heme Synthase Inhibitor On Hypoxia-inducedmentioning
confidence: 99%
“…We have also purified an NADPH-dependent cytochrome c reductase from the cytosolic fraction of HL-60 cells with a molecular mass of 68 kDa, and suggested that the enzyme might be released by limited proteolysis of the membrane-bound native form during its purification [7]. The isolation of the membrane-bound diaphorase to electrophoretic homogeneity was extremely difficult due to very low content and instability after solubilization from the membrane.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies we have described the presence of an NADPH diaphorase that contained FAD and FMN (1/1) as a prosthetic group in human neutrophils and differentiated HL-60 cells, and reported its characteristics [7][8][9][10]. We have also purified an NADPH-dependent cytochrome c reductase from the cytosolic fraction of HL-60 cells with a molecular mass of 68 kDa, and suggested that the enzyme might be released by limited proteolysis of the membrane-bound native form during its purification [7].…”
Section: Introductionmentioning
confidence: 99%